'Technologists' alongside : impact on student understandings in technology : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Education, Massey University, Palmerston North, New Zealand - Harwood, Cliff (Massey University, 2007)
This research focuses on ascertaining the impact of technologists working alongside students; in particular the influence their involvement has on their understandings of and about Technology. The research was conducted within an interpretive paradigm. Quantitative and qualitative data were gathered using a mixed methods approach which consisted of a written questionnaire, followed by purposive interviews. The participants in the study were students in years 11 and 12 in 2005. Data from these participants were also gathered in 2006. The research findings identified that when students work alongside a technologist(s) to resolve problems embedded within real-life contexts, their concepts of technology and its purpose are enhanced. These findings also highlighted the importance of ensuring that student learning intentions (those learning outcomes which are planned) are shared between all parties involved in the learning environment (teachers, practicing technologists and students), so that interactions between students and technologists have a positive influence on student learning. This research concludes that the involvement of practicing technologists, in student learning in technology education, offers the potential to enhance student's technological practice and their learning in technology generally.
Keywords: New Zealand; Technology; Study and teaching (Secondary); Experiential learning